Gender identity and female empowerment in the inhabitants of the Quinta Elena Neighborhood Association, 2020 - Navas Gómez, Heidy Cristina (2021)
The present study aimed to determine if there is a significant relationship between gender identity and female empowerment among the inhabitants of the residents of the Quinta Elena 2020 neighborhood association, an applied, quantitative research with a non-experimental-correlational design was used. cross-sectional section, with the sample consisting of 120 women from the Quinta Elena neighborhood association, the instrument “Questionnaire on attitudes towards gender identity (CAIG) - Modified” and the “Instrument for measuring empowerment in women (IMEN)". Finally, it was observed that gender identity is medium in 45.0%, in the same way, empowerment also registered a medium level in 74.2%, reaching the conclusion that there is a relationship between the variables evaluated (p <.05; r = .747) which demonstrates the proposed hypothesis.